2014
DOI: 10.2337/db13-1459
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA Methylation and Differential Expression of Genes Influencing Metabolism and Inflammation in Adipose Tissue From Subjects With Type 2 Diabetes

Abstract: Genetics, epigenetics, and environment may together affect the susceptibility for type 2 diabetes (T2D). Our aim was to dissect molecular mechanisms underlying T2D using genome-wide expression and DNA methylation data in adipose tissue from monozygotic twin pairs discordant for T2D and independent case-control cohorts. In adipose tissue from diabetic twins, we found decreased expression of genes involved in oxidative phosphorylation; carbohydrate, amino acid, and lipid metabolism; and increased expression of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
300
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 344 publications
(331 citation statements)
references
References 51 publications
27
300
2
2
Order By: Relevance
“…It should be noted that we previously identified extensive epigenetic alterations in human adipose tissue from other cohorts of a similar size to the one included in this study [9,11]. These studies together with our post hoc power calculation suggest an appropriate statistical power in the present study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…It should be noted that we previously identified extensive epigenetic alterations in human adipose tissue from other cohorts of a similar size to the one included in this study [9,11]. These studies together with our post hoc power calculation suggest an appropriate statistical power in the present study.…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, we recently found that ELOVL6, FADS1, FADS2 and GYS2 are among the most strongly downregulated genes in SAT from monozygotic twins discordant for type 2 diabetes [9]. In addition, the gene sets that were most significantly upregulated by HFO in this study (oxidative phosphorylation, citrate cycle and pyruvate metabolism) were significantly downregulated in SAT from diabetic twins [9]. A disturbed adipocyte metabolism has been suggested to shift lipid storage into alternative tissues, such as skeletal muscle, the liver and the pancreas, resulting in insulin resistance [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on adipose tissue from monozygotic twins discordant for T2DM (diabetics vs. non-diabetics) reported increased expression of inflammatory genes, such as secreted phosphoprotein (SPP)1 (also known as osteopontin, OPN), chemokine (C-C motif) ligand (CCL)18 and IL1RN, in association with variations of global and localized DNA methylation. 43 Moreover, the methylation of 7 CpGs in the promoter of the gene coding for the inflammatory molecule Toll-like receptor (TLR)-2 was significantly lower in T2DM patients compared with controls, and this difference was associated with marked variation in the composition of gut microbiota. 44 Inflammation has also been recognized as the pathogenic link between obesity and T2DM.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…1). 43 Epigenetics could be extremely important also in the inflammatory response of the hypertrophic adipose tissue in obese people. Remarkably, lean and obese individuals present differentially expressed miRNAs in their adipose tissue.…”
Section: B-cell Development and Functionmentioning
confidence: 99%